Cement strength stabilizing material, oil well cementing cement slurry system and application thereof

By using a mixture of quartz sand and glass powder as well as a mixture of minerals such as spodumene in cement strength stabilizing materials, the transformation of hydration products is inhibited and the generation of dense silicate minerals is promoted, thus solving the problem of cement stone strength and strength under high temperature conditions. The problem of unstable porosity and permeability parameters enables efficient cementing in deep or heavy oil steam huff and puff environments.

CN119330621AActive Publication Date: 2025-01-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310894804.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-21
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

The prior art cannot effectively maintain the strength and pore seepage parameters of cement stone under high temperature conditions, resulting in cement stone losing its interlayer sealing capacity in high-temperature cementing environments such as deep or heavy oil steam throughput, causing external traversal of water layer pipes. flow.

Method used

The use of a cement intensity stable material, which includes a mixture of quartz sand and glass powder as the first intensity stable material, and mixture of minerals such as pyroxyl, red pillar stone as the second intensity stable material, and inhibit the hydrophilic products through synergy. The transformation of the silicate mineral that promotes the dense structure.

Benefits of technology

Under the high temperature conditions of 200-350 ° C, the pressure resistance of cement stones has increased significantly, and it continues to grow steadily with the maintenance time, maintaining long-term intensity and hole seepage parameters stable, suitable for deep wells, ultra-deep wells, and thick oil steam hot well-collecting wells Fixed well application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004349369220000131
    Figure BDA0004349369220000131
  • Figure BDA0004349369220000141
    Figure BDA0004349369220000141
  • Figure BDA0004349369220000142
    Figure BDA0004349369220000142
Patent Text Reader

Abstract

The invention relates to the field of oil and gas well cementing engineering, and discloses a cement strength stabilizing material, an oil well cementing cement slurry system and application thereof. The cement strength stabilizing material comprises 30-80 parts by weight of a first strength stabilizing material and 20-70 parts by weight of a second strength stabilizing material, wherein the first strength stabilizing material is a mixture of quartz sand and glass powder; and the second strength stabilizing material is a mixture of at least two of spodumene, andalusite, olivine, leucite, garnet, grandalite, granite, garnet, nepheline, cross stone, spinel and graphite, and the second strength stabilizing material is a mixture of at least two of the spodumene, the andalusite, the olivine, the leucite, the garnet, the granite, the beryl, the nepheline, the cross stone, the spinel and the graphite. A cement slurry system containing the cement strength stabilizing material is suitable for working conditions of high-temperature direct forming such as deep wells and ultra-deep wells, is also suitable for working conditions of low-temperature forming and high-temperature service such as heavy oil steam exploitation, has good comprehensive performance and has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil and gas well cementing engineering, and in particular to a cement strength stabilizing material, an oil well cementing cement slurry system and applications thereof. Background Art

[0002] As oil and gas exploration continues to develop into deep and ultra-deep layers, oil and gas drilling encounters more and more complex formations, and the formation temperature and pressure are getting higher and higher. Domestic and foreign scholars have realized that high temperature is the main factor affecting the strength decline of cement paste. There is a temperature threshold. When the threshold is exceeded, the strength of cement paste begins to decrease significantly, which is extremely unfavorable for high-temperature well cementing. When the temperature reaches 110°C, the strength will decrease, and when it reaches 230°C, the cement paste may completely lose its strength.

[0003] my country has rich heavy oil resources and adopts steam-throwing development technology. The steam-throwing temperature can reach 350°C. The strength of the cement ring of conventional cementing declines, and after 1-2 cycles of steam-throwing, the interlayer isolation ability is lost, causing water layer to flow out of the pipe. The wells have to be scrapped. Some wells have steam "bubbling" on the ground, seriously affecting safety.

[0004] Therefore, there is an urgent need for a material that can maintain long-term stability in cement paste strength and porosity parameters under ultra-high temperature (200-350°C) conditions, so that cement paste can adapt to high-temperature cementing requirements such as deep or heavy oil steam huff and puff. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem in the prior art that the strength of cement stone decreases and the permeability increases due to the transformation of hydration products under high temperature conditions in sand-added oil well cement, and to provide a cement strength stabilizing material, an oil well cementing cement slurry system and applications thereof.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a cement strength stabilizing material, the cement strength stabilizing material comprising: 30-80 parts by weight of a first strength stabilizing material and 20-70 parts by weight of a second strength stabilizing material; wherein:

[0007] The first strength stabilizing material is a mixture of quartz sand and glass powder;

[0008] The second strength-stabilizing material is a mixture of at least two selected from spodumene, andalusite, olivine, leucite, garnet, pyrope, almandine, garnet, beryl, nepheline, staurolite, spinel and graphite.

[0009] A second aspect of the present invention provides an oil well cementing cement slurry system, wherein the cement slurry system comprises the cement strength stabilizing material provided by the present invention.

[0010] A third aspect of the present invention provides an application of the cement slurry system provided by the present invention in cementing a high-temperature deep well or a heavy oil steam thermal recovery well.

[0011] Through the above technical solution, the beneficial effects of the present invention are:

[0012] The cement strength stabilizing material of the present invention, on the one hand, provides sufficient silicon sources for cement hydration in the early and medium- to long-term through the synergistic effect of crystalline silicon and amorphous silicon, inhibits the formation of hydrated dicalcium silicate, and promotes the formation of tobermorite; on the other hand, a second high-temperature strength stabilizing material is used to inhibit the coarsening and degradation of xonotlite, prompting it to be transformed into a magnesium-aluminum-iron-calcium silicate mineral with a dense structure and long-term stable performance, thereby maintaining the long-term stability of the strength and porosity parameters of the cement stone. Whether it is formed in a low-temperature molding and high-temperature curing environment (molding at 40-80°C and curing at 300-350°C), or a high-temperature direct molding environment (molding and curing at 200-240°C), the cement stone formed after the cement slurry system provided by the present invention is formed has a high compressive strength, and continues to grow steadily with the curing time.

[0013] The preparation method of the cement strength stabilizing material of the present invention is simple, and does not require high-temperature calcination, hydrothermal treatment, acid-base modification and other operations, and can be directly mixed and stirred.

[0014] The cement slurry system of the present invention is suitable for high-temperature direct molding working conditions such as deep wells and ultra-deep wells, and is also suitable for low-temperature molding and high-temperature service working conditions such as heavy oil steam extraction. The cement slurry density and thickening time are adjustable, the flowability is good, the water loss is small, the strength is high, and it does not decay for a long time, and it fully meets the technical requirements of on-site cementing construction. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0016] The first aspect of the present invention provides a cement strength stabilizing material, the cement strength stabilizing material comprising: 30-80 parts by weight of a first strength stabilizing material and 20-70 parts by weight of a second strength stabilizing material; wherein:

[0017] The first strength stabilizing material is a mixture of quartz sand and glass powder;

[0018] The second strength-stabilizing material is a mixture of at least two selected from spodumene, andalusite, olivine, leucite, garnet, pyrope, almandine, garnet, beryl, nepheline, staurolite, spinel and graphite.

[0019] On the one hand, the first strength stabilizing material in the cement strength stabilizing material of the present invention is a mixture of quartz sand and glass powder, wherein the quartz sand is crystalline silicon and the glass powder is amorphous silicon. The first strength stabilizing material provides sufficient silicon source for cement hydration in the early and medium-long term through the synergistic effect of crystalline silicon and amorphous silicon, can inhibit the generation of hydrated dicalcium silicate, promote the transformation of hydration products from hydrated calcium silicate to tobermorite, thereby inhibiting the phenomenon of strength reduction and permeability increase of cement stone; on the other hand, the use of the second strength stabilizing material can inhibit the coarsening and deterioration of xonotlite, and promote its transformation into a magnesium-aluminum-iron-calcium silicate mineral with a dense structure and long-term stable performance, thereby maintaining the long-term stability of cement stone strength and porosity parameters. The first strength stabilizing material and the second strength stabilizing material play a good synergistic role in maintaining the strength and permeability of cement stone.

[0020] According to the present invention, preferably, the average particle size of the quartz sand is 3-198 μm, and the average particle size of the glass powder is 3-198 μm.

[0021] Furthermore, the average particle size of the quartz sand is 90-110 μm, and the average particle size of the glass powder is 30-60 μm.

[0022] According to the present invention, preferably, the weight ratio of the quartz sand to the glass powder is (0.2-5):1, preferably (1-2):1.

[0023] According to the present invention, preferably, the average particle size of the second strength stabilizing material is 10-165 μm, preferably 20-80 μm. If the average particle size of the second strength stabilizing material is too small, the obtained slurry will be more viscous, and if the average particle size is too large, the slurry will settle.

[0024] According to the present invention, preferably, the second strength-stabilizing material is a mixture of spodumene, leucite and graphite, or a mixture of andalusite and garnet, or a mixture of nepheline, spinel and graphite.

[0025] According to the present invention, preferably, the second strength stabilizing material is a mixture of spodumene with an average particle size of 30-60 μm, white garnet with an average particle size of 50-80 μm and graphite with an average particle size of 20-50 μm, or a mixture of andalusite with an average particle size of 30-60 μm and garnet with an average particle size of 30-60 μm, or a mixture of nepheline with an average particle size of 30-60 μm, spinel with an average particle size of 50-80 μm and graphite with an average particle size of 20-50 μm.

[0026] According to the present invention, preferably, when the second strength-stabilizing material is a mixture of spodumene, leucite and graphite, the weight ratio of spodumene, leucite and graphite is (7-14): (7-14): 1;

[0027] When the second strength-stabilizing material is a mixture of andalusite and garnet, the weight ratio of andalusite to garnet is (0.5-2):1;

[0028] When the second strength-stabilizing material is a mixture of nepheline, spinel and graphite, the weight ratio of nepheline, spinel and graphite is (7-14):(7-14):1.

[0029] According to the present invention, preferably, the cement strength stabilizing material further comprises less than 10 parts by weight of a reinforcing and toughening material.

[0030] According to the present invention, preferably, the reinforcing and toughening material is selected from carbon nanotubes and / or fibers.

[0031] According to the present invention, preferably, the reinforcing and toughening material is selected from carbon nanotubes with an average diameter of 20-30 nm and an average length of 0.5-30 μm; and / or, selected from fibers with an average diameter of 5-10 μm and an average length of 1-15 mm.

[0032] According to the present invention, preferably, the fibers are selected from carbon fibers and / or basalt fibers.

[0033] According to the present invention, preferably, the fiber is selected from carbon fibers having an average diameter of 5-8 μm and an average length of 1-15 mm; and / or, selected from basalt fibers having an average diameter of 5-10 μm and an average length of 3-15 mm.

[0034] According to the present invention, preferably, the cement strength stabilizing material comprises: 40-70 parts by weight of a first strength stabilizing material, 30-60 parts by weight of a second strength stabilizing material and 0.2-1 parts by weight of a reinforcing and toughening material.

[0035] According to the present invention, preferably, in the cement strength stabilizing material, the weight ratio of the first strength stabilizing material to the second strength stabilizing material is (1-2.3):1.

[0036] According to the present invention, preferably, the preparation method of the cement strength stabilizing material comprises the following steps: mixing the first strength stabilizing material and the second strength stabilizing material to obtain a first mixed material; and then mixing the first mixed material with the reinforcing and toughening material to obtain a cement strength stabilizing material.

[0037] A second aspect of the present invention provides an oil well cementing cement slurry system, wherein the cement slurry system comprises the cement strength stabilizing material provided by the present invention.

[0038] According to the present invention, preferably, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 35-100 parts of the cement strength stabilizing material, 4-10 parts of a fluid loss reducer, 1-12 parts of a retarder, 0.1-2 parts of a defoaming agent and 30-100 parts of water.

[0039] Furthermore, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 55-95 parts of the cement strength stabilizing material, 7-10 parts of fluid loss reducer, 2-11 parts of retarder, 0.4-0.6 parts of defoamer and 40-90 parts of water.

[0040] According to the present invention, preferably, the oil well cement is Grade G oil well cement.

[0041] According to the present invention, preferably, the fluid loss additive is a polymer.

[0042] According to the present invention, preferably, the polymer is a copolymer comprising a structural unit derived from 2-acrylamido-2-methylpropanesulfonic acid and a structural unit derived from acrylamide.

[0043] The present invention has no particular restrictions on the weight average molecular weight of the polymer and the weight ratio of the structural units derived from 2-acrylamido-2-methylpropanesulfonic acid and the structural units derived from acrylamide contained in the polymer, as long as the performance as a fluid loss reducer is satisfied. For example, a copolymer of AMPS and acrylamide purchased from Texas Continental Shelf with a brand name of SCF-J can be selected.

[0044] According to the present invention, preferably, the retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid multipolymer (AMPS multipolymer) and / or inorganic acid, preferably AMPS multipolymer. The present invention has no particular restrictions on the weight average molecular weight of the AMPS multipolymer and the proportion of the structural units contained in the AMPS multipolymer, as long as the performance as a retarder can be met. For example, an AMPS multipolymer purchased from Texas Continental Shelf with a brand name of SCR can be selected.

[0045] According to the present invention, preferably, the defoaming agent is selected from silicone defoaming agents and / or tributyl phosphate defoaming agents, preferably silicone defoaming agents.

[0046] According to the present invention, preferably, the cement slurry system further comprises: less than 2 parts by weight of a dispersant, preferably 0.4-0.6 parts by weight.

[0047] Preferably, the dispersant is selected from polycarboxylic acid dispersants and / or ketone-aldehyde condensates, preferably polycarboxylic acid dispersants. The present invention has no particular restrictions on the weight average molecular weight of the polycarboxylic acid dispersant, as long as it can meet the performance of the dispersant. For example, a polycarboxylic acid dispersant purchased from Texas Continental Shelf with a brand name of SCD can be selected.

[0048] According to the present invention, preferably, the cement slurry system further comprises: 3 parts by weight or less of a suspension stabilizer. The amount of the suspension stabilizer added is adjusted according to the density of the cement slurry system.

[0049] According to the present invention, preferably, the suspension stabilizer is selected from attapulgite and / or nano-silicon dioxide, preferably a mixture of attapulgite and nano-silicon dioxide.

[0050] According to the present invention, preferably, the weight ratio of attapulgite to nano-silicon dioxide is (2-4):1.

[0051] According to the present invention, preferably, the cement slurry system further comprises: 300 parts by weight or less of a density regulator. The amount of the density regulator added is adjusted according to the density of the cement slurry system.

[0052] According to the present invention, preferably, the density regulator is selected from at least one of iron ore powder, iron powder, manganese powder, barite, fly ash, slag and glass beads, preferably iron ore powder.

[0053] In the present invention, the function of the suspension stabilizer is to maintain the solid particles in the cement slurry system in a suspended state without precipitation; the function of the density regulator is to adjust the density of the cement slurry system. When the density of the cement slurry system is lower than 1.85 g / cm 3 Or higher than 1.95g / cm 3 It is necessary to add a density regulator and optionally a suspension stabilizer to obtain a density below 1.85 g / cm 3 Or higher than 1.95g / cm 3 cement slurry system.

[0054] According to a specific embodiment of the present invention, the cement slurry system includes the following components in parts by weight: 100 parts of oil well cement, 55-95 parts of the cement strength stabilizing material, less than 300 parts by weight of a density regulator, less than 3 parts by weight of a suspension stabilizer, 7-10 parts of a fluid loss additive, 2-11 parts of a retarder, 0.4-0.6 parts of a dispersant, 0.4-0.6 parts of a defoaming agent and 40-90 parts of water.

[0055] According to the present invention, preferably, when the cement slurry system has a density of 1.88-1.9 g / cm 3When the cement slurry system solidifies and is cured at 200-350°C for 28 days, the compressive strength is greater than or equal to 25 MPa.

[0056] According to a preferred embodiment of the present invention, when the cement slurry system has a density of 1.88-1.9 g / cm 3 When the cement slurry system solidifies and is cured at 200-350°C for 28 days, the compressive strength is greater than or equal to 40 MPa.

[0057] The third aspect of the present invention provides an application of the cement slurry system provided by the present invention in high-temperature deep well cementing. Whether it is formed in a low-temperature molding and high-temperature curing environment (molding at 40-80°C and curing at 300-350°C), or a high-temperature direct molding environment (molding and curing at 200-240°C), the cement stone formed by the cement slurry system provided by the present invention has a high compressive strength, and continues to grow steadily with the curing time.

[0058] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, all are conventional methods; the reagents and materials used, unless otherwise specified, can be obtained from commercial sources. The reagents and determination methods involved in the following examples and comparative examples are as follows:

[0059] The oil well cement was Grade G cement purchased from Jiahua Company;

[0060] Prepared according to GB / T 19139-2012 standard, density is 1.9-2.25g / cm 3 Cement slurry system;

[0061] The density of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0062] The fluidity of cement slurry system is determined according to the method specified in GB / T 8077-2012;

[0063] The API water loss of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0064] The thickening time of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0065] The compressive strength of the cement slurry system is determined according to the method specified in GB / T 19139-2012.

[0066] The following preparation example is used to illustrate the preparation of cement strength stabilizing material.

[0067] Preparation Example 1

[0068] 60 parts by weight of a first high-temperature strength stabilizing material (quartz sand with an average particle size of 100 μm and glass powder with an average particle size of 47 μm are mixed in a weight ratio of 1:1) and 40 parts by weight of a second high-temperature strength stabilizing material with an average particle size of 59 μm (spodumene with an average particle size of 47 μm, white garnet with an average particle size of 74 μm and graphite with an average particle size of 25 μm are mixed in a weight ratio of 10:10:1) and put into a blender for stirring and mixing until the mixture is uniform and no pseudo particles are observed with the naked eye; then the obtained mixed material is mixed with 0.2 parts by weight of a reinforcing and toughening material (multi-walled carbon nanotubes with an average diameter of 25 nm and an average length of 15 μm) and put into a blender for stirring and mixing until the mixture is uniform and no agglomerated particles are observed with the naked eye, thereby obtaining a cement strength stabilizing material, which is recorded as S1.

[0069] Preparation Example 2

[0070] 60 parts by weight of a first high-temperature strength stabilizing material (quartz sand with an average particle size of 100 μm and glass powder with an average particle size of 47 μm are mixed in a weight ratio of 1:1) and 40 parts by weight of a second high-temperature strength stabilizing material with an average particle size of 47 μm (andalusite with an average particle size of 47 μm and garnet with an average particle size of 47 μm are mixed in a weight ratio of 1:1) are mixed in a blender and stirred until the mixture is uniform and no pseudo particles are observed with the naked eye; then the obtained mixed material is mixed with 1 part by weight of a reinforcing and toughening material (carbon fiber with an average diameter of 6 μm and an average length of 8 mm) and stirred in a blender until the mixture is uniform and no agglomerated particles are observed with the naked eye, thereby obtaining a cement strength stabilizing material, which is recorded as S2.

[0071] Preparation Example 3

[0072] 60 parts by weight of a first high-temperature strength stabilizing material (quartz sand with an average particle size of 100 μm and glass powder with an average particle size of 47 μm are mixed in a weight ratio of 2:1) and 40 parts by weight of a second high-temperature strength stabilizing material with an average particle size of 59 μm (pyroxene with an average particle size of 47 μm, spinel with an average particle size of 74 μm and graphite with an average particle size of 25 μm are mixed in a weight ratio of 10:10:1) and put into a blender for stirring and mixing until the mixture is uniform and no pseudo particles are observed with the naked eye; then the obtained mixed material is mixed with 1 part by weight of a reinforcing and toughening material (basalt fiber with an average diameter of 7 μm and an average length of 8 mm) and put into a blender for stirring and mixing until the mixture is uniform and no agglomerated particles are observed with the naked eye, thereby obtaining a cement strength stabilizing material, which is recorded as S3.

[0073] Preparation Example 4

[0074] A cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight proportions of the first high temperature strength stabilizing material and the second high temperature strength stabilizing material were different. Specifically, the weight proportions of the first strength stabilizing material and the second strength stabilizing material in the cement strength stabilizing material were 30 parts and 70 parts, respectively. The obtained cement strength stabilizing material was recorded as S4.

[0075] Preparation Example 5

[0076] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the average particle sizes of the quartz sand and the glass powder were different. Specifically, the average particle size of the quartz sand was 47 μm, and the average particle size of the glass powder was 100 μm. The obtained cement strength stabilizing material was recorded as S5.

[0077] Preparation Example 6

[0078] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight ratio of quartz sand to glass powder was 3:1. The obtained cement strength stabilizing material was recorded as S6.

[0079] Preparation Example 7

[0080] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight ratio of quartz sand to glass powder was 6:1. The obtained cement strength stabilizing material was recorded as S7.

[0081] Preparation Example 8

[0082] A cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the second strength stabilizing material was a mixture of spodumene with an average particle size of 47 μm, andalusite with an average particle size of 47 μm, and graphite with an average particle size of 25 μm in a weight ratio of 10:10:1, to obtain a second high temperature strength stabilizing material with an average particle size of 46 μm. The obtained cement strength stabilizing material was recorded as S8.

[0083] Preparation Example 9

[0084] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight ratio of andalusite to garnet in the second high temperature strength stabilizing material was 3:1, and the second high temperature strength stabilizing material with an average particle size of 47 μm was obtained. The obtained cement strength stabilizing material was recorded as S9.

[0085] Preparation Example 10

[0086] A cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the average particle sizes of andalusite and garnet in the second high temperature strength stabilizing material were different. Specifically, andalusite with an average particle size of 75 μm and garnet with an average particle size of 100 μm were selected to obtain a second high temperature strength stabilizing material with an average particle size of 88 μm. The obtained cement strength stabilizing material was recorded as S10.

[0087] Preparation Example 11

[0088] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the second strength stabilizing material was andalusite with an average particle size of 47 μm. The obtained cement strength stabilizing material was recorded as S11.

[0089] Preparation Example 12

[0090] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight proportions of the first strength stabilizing material, the second strength stabilizing material and the reinforcing and toughening material were different. Specifically, the weight proportions of the first strength stabilizing material, the second strength stabilizing material and the reinforcing and toughening material in the cement strength stabilizing material were 80 parts, 20 parts and 0.2 parts respectively. The obtained cement strength stabilizing material was recorded as S12.

[0091] Preparation Example 13

[0092] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight portions of the first strength stabilizing material and the second strength stabilizing material were 40 parts and 60 parts respectively. The cement strength stabilizing material was obtained, which was recorded as S13.

[0093] Preparation Example 14

[0094] The cement strength stabilizing material was prepared according to the method of Preparation Example 2, except that the weight portions of the first strength stabilizing material and the second strength stabilizing material were 90 parts and 10 parts respectively. The cement strength stabilizing material was prepared and recorded as S14.

[0095] The following examples are used to illustrate the preparation of oil well cementing slurry systems.

[0096] Examples 1-13

[0097] Low temperature molding and high temperature curing environment (molding at 50°C and curing at 350°C), the cement slurry system contains the following components by weight: 100 parts of G-grade cement, 80 parts of cement strength stabilizer S1-S13, 3 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 52-65 parts of clean water (the density of cement strength stabilizer S1-S13 is different, and clean water is used to adjust the density of the cement slurry system), and the obtained density is 1.9g / cm 3 cement slurry system.

[0098] In a high temperature direct molding environment (molding and curing at 240°C), the cement slurry system contains the following components by weight: 100 parts of G-grade cement, 80 parts of cement strength stabilizer S1-S13, 10 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 45-58 parts of clean water, and the obtained density is 1.9g / cm 3 cement slurry system.

[0099] Among them, the retarder is an AMPS multipolymer purchased from Texas Continental Shelf with the brand name SCR;

[0100] The fluid loss additive was a copolymer of AMPS and acrylamide, purchased from Texas Shelf, with the brand name SCF-J;

[0101] The defoamer is a polysiloxane silicone defoamer purchased from Texas Shelf with a brand name of SCFD-2.

[0102] Examples 14-15

[0103] Low temperature molding and high temperature curing environment (molding at 50°C and curing at 350°C), the cement slurry system comprises the following components by weight: 100 parts of G-grade cement, 80 parts of cement strength stabilizer (S2, S4), 80 parts of density regulator (iron ore powder), 1 part of suspension stabilizer (attapulgite and nano-silicon dioxide mixed in a weight ratio of 3:1), 3 parts of retarder, 9 parts of fluid loss additive, 0.5 parts of dispersant, 0.5 parts of defoamer and 51-62 parts of clean water, and the obtained density is 2.25g / cm 3 cement slurry system.

[0104] In a high temperature direct molding environment (molding and curing at 240°C), the cement slurry system comprises the following components by weight: 100 parts of G-grade cement, 80 parts of cement strength stabilizer (S2, S4), 80 parts of density regulator (iron ore powder), 2 parts of suspension stabilizer (attapulgite and nano-silicon dioxide mixed in a weight ratio of 3:1), 10 parts of retarder, 9 parts of fluid loss additive, 0.5 parts of dispersant, 0.5 parts of defoamer and 44-55 parts of clean water, and the obtained density is 2.25g / cm 3 cement slurry system.

[0105] Wherein, the dispersant is a polycarboxylic acid dispersant purchased from Texas Continental Shelf with a brand name of SCD; the retarder, fluid loss agent and defoamer are the same as those in Example 1.

[0106] Comparative Example 1

[0107] The cement slurry system was prepared according to the method of Example 2, except that the cement strength stabilizing material S14 was selected to replace the cement strength stabilizing material S2 of the same mass.

[0108] Comparative Example 2

[0109] The cement slurry system was prepared according to the method of Example 2, except that quartz sand with an average particle size of 100 μm was used to replace the cement strength stabilizing material S2 of the same mass. The cement slurry system was prepared.

[0110] Comparative Example 3

[0111] The cement slurry system was prepared according to the method of Example 14, except that the cement strength stabilizing material S14 was selected to replace the cement strength stabilizing material S2 of the same mass. The cement slurry system was prepared.

[0112] Comparative Example 4

[0113] The cement slurry system was prepared according to the method of Example 14, except that quartz sand with an average particle size of 100 μm was used to replace the cement strength stabilizing material S2 of the same mass. The cement slurry system was prepared.

[0114] Test Case

[0115] The density and fluidity of the cement slurry system at room temperature, and the API water loss and thickening time at 220°C of the cement slurry system prepared in each embodiment and comparative example in a high temperature direct molding environment (molding and curing at 240°C) were measured respectively, and the results are shown in Table 1; and the development of the compressive strength of the formed cement stone in low temperature molding, high temperature curing environment (molding at 50°C and curing at 350°C) and high temperature direct molding environment, respectively, are shown in Table 2.

[0116] Table 1

[0117]

[0118]

[0119] Table 2

[0120]

[0121] Note: In low-temperature molding and high-temperature curing environments, the molding and curing pressures are both 21MPa; in high-temperature direct molding environments, the molding and curing pressures are both 21MPa.

[0122] As shown in Table 1, the cement slurry system of the present invention has good comprehensive performance and meets the requirements of ultra-high temperature deep well or heavy oil cementing construction. As shown in Table 2, Comparative Examples 2 and 4 use quartz sand as cement strength stabilizing material. Whether it is low-temperature molding, high-temperature curing environment, or high-temperature direct molding environment, there is strength decay under high temperature conditions. Using the cement strength stabilizing material of the present invention, the strength of cement stone is high under two service environments, and it continues to grow steadily.

[0123] In addition, Example 4 and Example 12 changed the weight fractions of each component in the cement strength stabilizing material, Example 5 changed the average particle size of quartz sand and glass powder, Example 6 and Example 7 changed the weight ratio of quartz sand and glass powder, Example 8 and Example 11 changed the composition of the second strength stabilizing material, Example 9 changed the weight ratio of andalusite and garnet in the second high-temperature strength stabilizing material, Example 10 changed the average particle size of the second high-temperature strength stabilizing material, and Example 13 changed the ratio of the first strength stabilizing material to the second strength stabilizing material. Compared with Example 2, whether it is low-temperature molding, high-temperature curing environment, or high-temperature direct molding environment, the strength of the cement paste is reduced, but the strength of the cement paste continues to increase after curing. This shows that the ratio of each component in the cement strength stabilizing material, the average particle size and weight ratio of quartz sand and glass powder, the composition of the second strength stabilizing material, the ratio of each component and the average particle size have a certain influence on the strength of the obtained cement paste.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cement strength stabilizing material, characterized in that: The cement strength stabilizing material comprises: 30-80 parts by weight of a first strength stabilizing material and 20-70 parts by weight of a second strength stabilizing material; wherein: The first strength stabilizing material is a mixture of quartz sand and glass powder; The second strength-stabilizing material is a mixture of at least two selected from spodumene, andalusite, olivine, leucite, garnet, pyrope, almandine, garnet, beryl, nepheline, staurolite, spinel and graphite.

2. The cement strength stabilizing material according to claim 1, characterized in that: The average particle size of the quartz sand is 3-198 μm, preferably 90-110 μm; the average particle size of the glass powder is 3-198 μm, preferably 30-60 μm; Preferably, the weight ratio of the quartz sand to the glass powder is (0.2-5):1, preferably (1-2):

1.

3. The cement strength stabilizing material according to claim 1 or 2, characterized in that: The average particle size of the second strength stabilizing material is 10-165 μm, preferably 20-80 μm.

4. The cement strength stabilizing material according to any one of claims 1 to 3, characterized in that: The second strength-stabilizing material is a mixture of spodumene, leucite and graphite, or a mixture of andalusite and garnet, or a mixture of nepheline, spinel and graphite; Preferably, the second strength stabilizing material is a mixture of spodumene with an average particle size of 30-60 μm, white garnet with an average particle size of 50-80 μm and graphite with an average particle size of 20-50 μm, or a mixture of andalusite with an average particle size of 30-60 μm and garnet with an average particle size of 30-60 μm, or a mixture of nepheline with an average particle size of 30-60 μm, spinel with an average particle size of 50-80 μm and graphite with an average particle size of 20-50 μm.

5. The cement strength stabilizing material according to claim 4, characterized in that: When the second strength-stabilizing material is a mixture of spodumene, leucite and graphite, the weight ratio of spodumene, leucite and graphite is (7-14): (7-14): 1; When the second strength-stabilizing material is a mixture of andalusite and garnet, the weight ratio of andalusite to garnet is (0.5-2):1; When the second strength-stabilizing material is a mixture of nepheline, spinel and graphite, the weight ratio of nepheline, spinel and graphite is (7-14):(7-14):

1.

6. The cement strength stabilizing material according to any one of claims 1 to 5, characterized in that: The cement strength stabilizing material also includes less than 10 parts by weight of a reinforcing and toughening material; Preferably, the reinforcing and toughening material is selected from carbon nanotubes and / or fibers; Preferably, the average diameter of the carbon nanotubes is 20-30 nm, and the average length is 0.5-30 μm; the average diameter of the fibers is 5-10 μm, and the average length is 1-15 mm; Preferably, the fibers are selected from carbon fibers and / or basalt fibers; Preferably, the cement strength stabilizing material comprises: 40-70 parts by weight of a first strength stabilizing material, 30-60 parts by weight of a second strength stabilizing material, and 0.2-1 parts by weight of a reinforcing and toughening material; Preferably, in the cement strength stabilizing material, the weight ratio of the first strength stabilizing material to the second strength stabilizing material is (1-2.3):

1.

7. An oil well cementing slurry system, characterized in that: The cement slurry system comprises the cement strength stabilizing material according to any one of claims 1 to 6; Preferably, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 35-100 parts of the cement strength stabilizing material, 4-10 parts of fluid loss reducer, 1-12 parts of retarder, 0.1-2 parts of defoamer and 30-100 parts of water.

8. The cement slurry system according to claim 7, characterized in that: The fluid loss additive is a polymer; Preferably, the polymer is a copolymer comprising structural units derived from 2-acrylamido-2-methylpropanesulfonic acid and structural units derived from acrylamide; Preferably, the retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid multipolymer and / or inorganic acid, preferably 2-acrylamide-2-methylpropanesulfonic acid multipolymer; Preferably, the defoamer is selected from silicone defoamers and / or tributyl phosphate defoamers, preferably silicone defoamers; Preferably, the cement slurry system further comprises: 2 parts by weight or less of a dispersant; Preferably, the dispersant is selected from polycarboxylic acid dispersants and / or ketone-aldehyde condensates, preferably polycarboxylic acid dispersants.

9. The cement slurry system according to claim 7 or 8, characterized in that: The cement slurry system further includes: 3 parts by weight or less of a suspension stabilizer; Preferably, the suspension stabilizer is selected from attapulgite and / or nano-silicon dioxide, preferably a mixture of attapulgite and nano-silicon dioxide; Preferably, the weight ratio of attapulgite to nano-silicon dioxide is (2-4):

1.

10. The cement slurry system according to any one of claims 7 to 9, characterized in that: The cement slurry system further includes: 300 parts by weight or less of a density regulator; Preferably, the density regulator is selected from at least one of iron ore powder, iron powder, manganese powder, barite, fly ash, slag and glass beads, preferably iron ore powder.

11. The cement slurry system according to any one of claims 7 to 10, characterized in that: When the cement slurry system has a density of 1.88-1.9 g / cm 3 When the cement slurry system solidifies and is cured at 200-350°C for 28 days, the compressive strength is greater than or equal to 25 MPa; Preferably, when the cement slurry system has a density of 1.88-1.9 g / cm 3 When the cement slurry system solidifies and is cured at 200-350°C for 28 days, the compressive strength is greater than or equal to 40 MPa.

12. Use of the cement slurry system according to any one of claims 7 to 11 in cementing of high-temperature deep wells or heavy oil steam thermal recovery wells.

Citation Information

Patent Citations

  • High-strength high-toughness high-temperature-resistant oil well cement slurry system as well as preparation method and design method thereof

    CN106833567A

  • Oil well cement with high temperature resistance and strength decline inhibition as well as preparation method and application of oil well cement

    CN113683354A

  • Large-temperature-difference well cementation cement paste and preparation method thereof

    CN114380540A

  • Suspension stabilizer as well as preparation method and application thereof

    CN115772009A